A hydrophilic aluminum foil for air conditioner radiator
By using an aluminum foil body and protective layer on the air conditioner heat sink, the problem of hydrophilic aluminum foil paint falling off is solved, and the lasting hydrophilicity and corrosion resistance are achieved, and the heat dissipation effect and service life are improved.
Patent Information
- Application Number
- CN202411780187.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-04
AI Technical Summary
After a long time of use, the hydrophilic aluminum foil on the existing air conditioner heat sink is easily peeled off, resulting in a reduced heat dissipation effect and cannot meet the usage requirements.
The design is adopted for an aluminum foil body plus a protective layer, wherein the protective layer includes an anticorrosion layer and a photocurable hydrophilic layer. The anticorrosion layer is arranged on the outer surface of the aluminum foil by thermal spraying, and the photocurable hydrophilic layer is coated on the outside of the anticorrosion layer, and is photocured by a curing machine.
The long-lasting hydrophilicity and corrosion resistance of aluminum foil are achieved, the problem of paint falling off is avoided, and the service life and heat dissipation effect of the heat sink are improved.
Smart Images

Figure CN119747186A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of air conditioner radiator processing, and in particular to a hydrophilic aluminum foil for an air conditioner radiator. Background Art
[0002] The air conditioner radiator, also known as the condenser, is one of the important components used to dissipate heat in the air conditioner. It is usually made of copper tubes and aluminum sheets, and its function is to exchange heat from the refrigerant in the air conditioner, turning it from gas to liquid.
[0003] When the air conditioner is working, it will generate a lot of heat. If it is not dissipated in time, its cooling effect will be seriously affected. The function of the air conditioner heat sink is to quickly dissipate the heat absorbed by the refrigerant through heat exchange, ensuring the stability of the temperature and pressure inside the air conditioner, thereby improving the cooling effect of the air conditioner.
[0004] With the progress of society, the air-conditioning industry has developed rapidly. For air-conditioning radiators, the raw material of air-conditioning radiators is now hydrophilic aluminum foil, which can increase the cooling efficiency by 5%. It also has the functions of anti-corrosion and anti-mildew, and has no odor. It will not cause the accumulation of water droplets to block the heat exchange.
[0005] The existing patent application publication number is CN114798388B, and the patent name is an invention patent of a super hydrophilic antibacterial aluminum foil. The invention patent records the following steps: cleaning the aluminum sheet to remove the oxide layer, placing it in a hexamethylenetetramine solution, reacting at 180°C for 1.5 hours, taking it out and drying it at 60°C, 100°C, 200°C, 300°C and 400°C for 1 hour to obtain a substrate; preparing the following raw materials by weight: 25-30 parts of methoxy polyethylene glycol acrylate, 30-50 parts of water-based polyurethane acrylate oligomer, 6-12 parts of ethoxylated trimethylolpropane triacrylate, 5-8 parts of modified silica and 2-3 parts of photoinitiator, mixing the raw materials in the second step, and adding water to dilute it to prepare a resin solution with a mass fraction of 1%, applying the resin solution to the surface of the substrate, and curing it to obtain a super hydrophilic antibacterial aluminum foil, whose initial water contact angle is less than 5°, the adhesion grade is 0, and it has high lasting hydrophilicity and antibacterial properties.
[0006] The above-mentioned production scheme is the same as the existing one, which directly coats the hydrophilic coating on the outer surface of the aluminum foil whose surface has been cleaned or the aluminum foil with an oxide layer applied. The hydrophilic aluminum foil produced in this way can cope with ordinary environments, but when used for heat sinks, the temperature on the heat sink changes greatly, and it is exposed to the outside world. After long-term use, the hydrophilic coating will fall off, so that the hydrophilic aluminum foil has the same function as ordinary aluminum foil, which reduces the heat dissipation effect and does not meet people's use requirements. For this reason, we propose a hydrophilic aluminum foil for air conditioner heat sinks. Summary of the invention
[0007] The main purpose of the present invention is to provide a hydrophilic aluminum foil for air conditioner radiating fins, which can effectively solve the problems in the background technology.
[0008] To achieve the above object, the technical solution adopted by the present invention is:
[0009] A hydrophilic aluminum foil for an air conditioner heat sink comprises an aluminum foil body and a protective layer arranged on the outside of the aluminum foil body, wherein the protective layer comprises an anti-corrosion layer and a photocurable hydrophilic layer, wherein the anti-corrosion layer is arranged on the outer surface of the aluminum foil body by thermal spraying, and the photocurable hydrophilic layer is coated on the outside of the anti-corrosion layer and is photocured by a curing machine.
[0010] Preferably, the hydrophilic layer includes a base layer and a hydrophilic surface layer, the base layer is coated on the outside of the anti-corrosion layer, and after the base layer is cured, the hydrophilic surface layer is coated on the outside of the base layer.
[0011] Preferably, the preparation steps of the hydrophilic aluminum foil for air conditioner radiator are as follows:
[0012] S1. Select an aluminum foil body of standard size and then pre-treat the aluminum foil body;
[0013] S2, spraying the anti-corrosion coating on the outer surface of the aluminum foil body by thermal spraying;
[0014] S3, high temperature curing anticorrosive layer;
[0015] S4, coating a base layer on the outside of the anti-corrosion layer and curing to form a base film;
[0016] S5. Coating a hydrophilic surface layer on the outer side of the base film and performing light curing.
[0017] Preferably, the steps of pre-treating the aluminum foil body in step S1 are as follows:
[0018] After immersing the aluminum foil in a 5% NaOH solution for 25-40 seconds, rinse the aluminum foil with deionized water for 2-5 minutes;
[0019] The rinsed aluminum foil is soaked in a 30% nitric acid solution for 50-65 seconds, then rinsed with deionized water for 2-5 minutes, and then air-dried.
[0020] Preferably, in step S2, the anti-corrosion coating is sprayed on the outer surface of the aluminum foil body using plasma spraying technology.
[0021] Preferably, when the anti-corrosion layer is cured at high temperature in step S3, the product is placed at 100° C. for 20-25 minutes, and then placed at 150-300° C. for 1-2 hours to obtain a cured anti-corrosion layer.
[0022] Preferably, the anticorrosive coating comprises the following components in parts by weight: 18-20 parts of silicone resin, 25-35 parts of polyurethane resin, 6-8 parts of nano titanium dioxide and 3-5 parts of nano aluminum powder, 2-10 parts of curing agent, 8-15 parts of diluent and 10-20 parts of deionized water;
[0023] The curing agent is polyamide resin, and the diluent is any one of diethylene glycol ethyl ether and butyl acetate.
[0024] Preferably, the bottom layer in step S4 is coated with acrylic resin on the outer surface of the cured anti-corrosion layer, and after coating, it is placed at 100° C. for curing for 30-50 minutes.
[0025] Preferably, in step S5, the hydrophilic surface layer is formed by coating with a photosensitive hydrophilic acrylic resin. When coating the photosensitive hydrophilic acrylic resin, a coater is first used to coat the photosensitive hydrophilic acrylic resin on the outer surface of the bottom layer, and then a curing agent is used to cure the coated photosensitive hydrophilic acrylic resin to obtain a hydrophilic surface layer. The thickness of the hydrophilic surface layer is 40-60 microns, and the thickness of the bottom layer is 20-30 microns.
[0026] Preferably, the preparation steps of the photosensitive hydrophilic acrylic resin are as follows:
[0027] A. Add solvent to the reaction vessel and heat the reaction vessel to 50-60°C;
[0028] B. adding an initiator to a hydrophilic monomer to form a mixed solution;
[0029] C. Add the mixed solution into a reaction vessel for polymerization reaction, and keep the polymerization temperature for 2.5-3 hours to obtain an acrylate copolymer;
[0030] D. Adding a catalyst, a polymerization inhibitor and a photosensitive monomer to the acrylate copolymer, and heating the reaction container to 120-130° C. to obtain a photosensitive hydrophilic acrylic resin after reaction;
[0031] The solvent is a mixed solvent of ethylene glycol monomethyl ether and toluene in a weight ratio of 1:1:
[0032] The hydrophilic monomers are acrylic acid, hydroxypropyl acrylate and butyl acrylate in a weight ratio of 36:65:64;
[0033] The initiator is an azo initiator, and the initiator is one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate;
[0034] The catalyst is one of chiral thiourea and tetrabutylammonium bromide;
[0035] The polymerization inhibitor is one of hydroquinone, tert-butylcatechol and copper naphthenate;
[0036] The photosensitive monomer is glycidyl methacrylate.
[0037] Compared with the prior art, the hydrophilic aluminum foil for air conditioner radiator of the present invention has the following beneficial effects:
[0038] First, the present invention records a hydrophilic aluminum foil for air conditioner heat sinks, which uses epoxy acrylic resin with simple raw material sources and simple synthesis process as the main raw material, and uses a light-curing hydrophilic coating, which has a low curing temperature and relatively low production requirements, and can significantly reduce production costs. At the same time, less solvent is required in the production process, and the overall use is relatively environmentally friendly.
[0039] Secondly, the present invention records a hydrophilic aluminum foil for air conditioner heat sinks, wherein the hydrophilic coating is formed by combining a bottom layer with a hydrophilic surface layer, and both the bottom layer and the hydrophilic surface layer are based on acrylic resin, and the two have good compatibility, which is beneficial for the hydrophilic surface layer to penetrate into the bottom film, resulting in better adhesion. The foil will not fall off after long-term use, and the use effect is good.
[0040] Third, the present invention records a hydrophilic aluminum foil for air conditioner heat sinks, which has strong overall hydrophilicity. When in use, the initial water contact angle is less than 5°, and it has long-lasting continuous hydrophilicity. It also has a good heat resistance limit, can effectively avoid changes and cracking problems caused by high temperature, has good use effect, and has good use prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The present invention is a flow chart of a production process of a hydrophilic aluminum foil for air conditioner radiating fins. DETAILED DESCRIPTION
[0042] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further explained below in conjunction with specific implementation methods.
[0043] Example 1
[0044] A hydrophilic aluminum foil for an air conditioner heat sink comprises an aluminum foil body and a protective layer arranged on the outside of the aluminum foil body, wherein the protective layer comprises an anti-corrosion layer and a photocurable hydrophilic layer, wherein the anti-corrosion layer is arranged on the outer surface of the aluminum foil body by thermal spraying, and the photocurable hydrophilic layer is coated on the outside of the anti-corrosion layer and is photocured by a curing machine.
[0045] The hydrophilic layer comprises a bottom layer and a hydrophilic surface layer. The bottom layer is coated on the outside of the anti-corrosion layer. After the bottom layer is cured, the hydrophilic surface layer is coated on the outside of the bottom layer.
[0046] The preparation steps of hydrophilic aluminum foil for air conditioner radiator are as follows:
[0047] S1. Select an aluminum foil body of standard size (standard width), and then pre-treat the aluminum foil body;
[0048] The steps for pre-treating the aluminum foil body are as follows:
[0049] After immersing the aluminum foil in 5% NaOH solution for 25 min, the aluminum foil was rinsed with deionized water for 3 min.
[0050] The rinsed aluminum foil was immersed in a 30% nitric acid solution for 55 seconds, then rinsed with deionized water for 3 minutes, and then air-dried.
[0051] S2, spraying the anti-corrosion coating on the outer surface of the aluminum foil body by thermal spraying;
[0052] The anti-corrosion coating is sprayed on the outer surface of the aluminum foil body by using plasma spraying technology;
[0053] In the process of plasma spraying, the base metal does not melt, the temperature is high but the energy is concentrated, the aluminum foil will not be deformed, the spraying is more uniform, and the use of plasma spraying does not require the use of organic solvents, reducing pollution to the environment. At the same time, the energy utilization rate of plasma spraying technology is high, which reduces energy waste. Further plasma spraying can achieve high-speed spraying, greatly improving production efficiency, good coating stability, and at the same time improving the bonding strength with the base, so that the anti-corrosion layer will not fall off easily.
[0054] S3, high temperature curing anticorrosive layer;
[0055] When the anti-corrosion layer is cured at high temperature, the product is placed at 100°C for 20 minutes, and then placed at 180°C for 1 hour to obtain a cured anti-corrosion layer.
[0056] The anticorrosive coating comprises the following components in parts by weight: 18 parts of organic silicon resin, 26 parts of polyurethane resin, 7 parts of nano titanium dioxide and 4 parts of nano aluminum powder, 6 parts of curing agent, 10 parts of diluent and 16 parts of deionized water;
[0057] The curing agent is polyamide resin, and the diluent is butyl acetate.
[0058] S4, coating a base layer on the outside of the anti-corrosion layer and curing to form a base film;
[0059] The bottom layer is made of acrylic resin paint on the outer surface of the cured anti-corrosion layer. After coating, it is placed at 100℃ for curing for 30-50 minutes.
[0060] S5. Coating a hydrophilic surface layer on the outer side of the base film and performing light curing.
[0061] The hydrophilic surface layer is coated with a photosensitive hydrophilic acrylic resin. When coating the photosensitive hydrophilic acrylic resin, a coater is first used to coat the photosensitive hydrophilic acrylic resin on the outer surface of the bottom layer, and then a curing agent is used to cure the coated photosensitive hydrophilic acrylic resin to obtain a hydrophilic surface layer. The thickness of the hydrophilic surface layer is 45 microns, and the thickness of the bottom layer is 20 microns.
[0062] The preparation steps of photosensitive hydrophilic acrylic resin are as follows:
[0063] A. Add solvent to the reaction vessel and heat the reaction vessel to 55°C;
[0064] B. adding an initiator to a hydrophilic monomer to form a mixed solution;
[0065] C. adding the mixed solution into a reaction vessel for polymerization reaction, and keeping the polymerization temperature for 2.5 hours to obtain an acrylate copolymer;
[0066] D. Adding a catalyst, a polymerization inhibitor and a photosensitive monomer to the acrylate copolymer, and heating the reaction container to 120° C. to obtain a photosensitive hydrophilic acrylic resin after reaction;
[0067] The solvent is a mixed solvent of ethylene glycol monomethyl ether and toluene in a weight ratio of 1:1:
[0068] The hydrophilic monomers are acrylic acid, hydroxypropyl acrylate and butyl acrylate in a weight ratio of 36:65:64;
[0069] The initiator is an azo initiator, and the initiator is azobisisoheptanonitrile;
[0070] The catalyst is chiral thiourea;
[0071] The inhibitor is hydroquinone;
[0072] The photosensitive monomer is glycidyl methacrylate.
[0073] Example 2
[0074] A hydrophilic aluminum foil for an air conditioner heat sink comprises an aluminum foil body and a protective layer arranged on the outside of the aluminum foil body, wherein the protective layer comprises an anti-corrosion layer and a photocurable hydrophilic layer, wherein the anti-corrosion layer is arranged on the outer surface of the aluminum foil body by thermal spraying, and the photocurable hydrophilic layer is coated on the outside of the anti-corrosion layer and is photocured by a curing machine.
[0075] The hydrophilic layer comprises a bottom layer and a hydrophilic surface layer. The bottom layer is coated on the outside of the anti-corrosion layer. After the bottom layer is cured, the hydrophilic surface layer is coated on the outside of the bottom layer.
[0076] The preparation steps of hydrophilic aluminum foil for air conditioner radiator are as follows:
[0077] S1. Select an aluminum foil body of standard size (standard width), and then pre-treat the aluminum foil body;
[0078] The steps for pre-treating the aluminum foil body are as follows:
[0079] After immersing the aluminum foil in 5% NaOH solution for 35 seconds, the aluminum foil was rinsed with deionized water for 4 minutes;
[0080] The rinsed aluminum foil was immersed in a 30% nitric acid solution for 60 seconds, then rinsed with deionized water for 4 minutes, and then air-dried.
[0081] S2, spraying the anti-corrosion coating on the outer surface of the aluminum foil body by thermal spraying;
[0082] The anti-corrosion coating is sprayed on the outer surface of the aluminum foil body by using plasma spraying technology;
[0083] In the process of plasma spraying, the base metal does not melt, the temperature is high but the energy is concentrated, the aluminum foil will not be deformed, the spraying is more uniform, and the use of plasma spraying does not require the use of organic solvents, reducing pollution to the environment. At the same time, the energy utilization rate of plasma spraying technology is high, which reduces energy waste. Further plasma spraying can achieve high-speed spraying, greatly improving production efficiency, good coating stability, and at the same time improving the bonding strength with the base, so that the anti-corrosion layer will not fall off easily.
[0084] S3, high temperature curing anticorrosive layer;
[0085] When the anti-corrosion layer is cured at high temperature, the product is placed at 100°C for 23 minutes and then at 200°C for 1.5 hours to obtain a cured anti-corrosion layer.
[0086] The anticorrosive coating comprises the following components in parts by weight: 19 parts of organic silicon resin, 30 parts of polyurethane resin, 7 parts of nano titanium dioxide and 4 parts of nano aluminum powder, 7 parts of curing agent, 12 parts of diluent and 17 parts of deionized water;
[0087] The curing agent is polyamide resin, and the diluent is diethylene glycol ethyl ether.
[0088] S4, coating a base layer on the outside of the anti-corrosion layer and curing to form a base film;
[0089] The bottom layer is made of acrylic resin paint on the outer surface of the cured anti-corrosion layer. After coating, it is placed at 100℃ for 40 minutes to cure.
[0090] S5. Coating a hydrophilic surface layer on the outer side of the base film and performing light curing.
[0091] The hydrophilic surface layer is coated with a photosensitive hydrophilic acrylic resin. When coating the photosensitive hydrophilic acrylic resin, a coater is first used to coat the photosensitive hydrophilic acrylic resin on the outer surface of the bottom layer, and then a curing agent is used to cure the coated photosensitive hydrophilic acrylic resin to obtain a hydrophilic surface layer. The thickness of the hydrophilic surface layer is 55 microns, and the thickness of the bottom layer is 25 microns.
[0092] The preparation steps of photosensitive hydrophilic acrylic resin are as follows:
[0093] A. Add solvent to the reaction vessel and heat the reaction vessel to 55°C;
[0094] B. adding an initiator to a hydrophilic monomer to form a mixed solution;
[0095] C. adding the mixed solution into a reaction vessel for polymerization reaction, and keeping the polymerization temperature for 3 hours to obtain an acrylate copolymer;
[0096] D. Adding a catalyst, a polymerization inhibitor and a photosensitive monomer to the acrylate copolymer, and heating the reaction container to 125° C. to obtain a photosensitive hydrophilic acrylic resin after reaction;
[0097] The solvent is a mixed solvent of ethylene glycol monomethyl ether and toluene in a weight ratio of 1:1:
[0098] The hydrophilic monomers are acrylic acid, hydroxypropyl acrylate and butyl acrylate in a weight ratio of 36:65:64;
[0099] The initiator is an azo initiator, and the initiator is azobisisobutyronitrile;
[0100] The catalyst is tetrabutylammonium bromide;
[0101] The inhibitor is hydroquinone;
[0102] The photosensitive monomer is glycidyl methacrylate.
[0103] Example 3
[0104] A hydrophilic aluminum foil for an air conditioner heat sink comprises an aluminum foil body and a protective layer arranged on the outside of the aluminum foil body, wherein the protective layer comprises an anti-corrosion layer and a photocurable hydrophilic layer, wherein the anti-corrosion layer is arranged on the outer surface of the aluminum foil body by thermal spraying, and the photocurable hydrophilic layer is coated on the outside of the anti-corrosion layer and is photocured by a curing machine.
[0105] The hydrophilic layer comprises a bottom layer and a hydrophilic surface layer. The bottom layer is coated on the outside of the anti-corrosion layer. After the bottom layer is cured, the hydrophilic surface layer is coated on the outside of the bottom layer.
[0106] The preparation steps of hydrophilic aluminum foil for air conditioner radiator are as follows:
[0107] S1. Select an aluminum foil body of standard size (standard width), and then pre-treat the aluminum foil body;
[0108] The steps for pre-treating the aluminum foil body are as follows:
[0109] After immersing the aluminum foil in 5% NaOH solution for 40 seconds, the aluminum foil was rinsed with deionized water for 4 minutes;
[0110] The rinsed aluminum foil was immersed in a 30% nitric acid solution for 60 seconds, then rinsed with deionized water for 5 minutes, and then air-dried.
[0111] S2, spraying the anti-corrosion coating on the outer surface of the aluminum foil body by thermal spraying;
[0112] The anti-corrosion coating is sprayed on the outer surface of the aluminum foil body by using plasma spraying technology;
[0113] In the process of plasma spraying, the base metal does not melt, the temperature is high but the energy is concentrated, the aluminum foil will not be deformed, the spraying is more uniform, and the use of plasma spraying does not require the use of organic solvents, reducing pollution to the environment. At the same time, the energy utilization rate of plasma spraying technology is high, which reduces energy waste. Further plasma spraying can achieve high-speed spraying, greatly improving production efficiency, good coating stability, and at the same time improving the bonding strength with the base, so that the anti-corrosion layer will not fall off easily.
[0114] S3, high temperature curing anticorrosive layer;
[0115] When the anti-corrosion layer is cured at high temperature, the product is placed at 100°C for 25 minutes, and then placed at 250°C for 1.2 hours to obtain a cured anti-corrosion layer.
[0116] The anticorrosive coating comprises the following components in parts by weight: 20 parts of organic silicon resin, 33 parts of polyurethane resin, 8 parts of nano titanium dioxide and 4 parts of nano aluminum powder, 8 parts of curing agent, 13 parts of diluent and 20 parts of deionized water;
[0117] The curing agent is polyamide resin, and the diluent is diethylene glycol ethyl ether.
[0118] S4, coating a base layer on the outside of the anti-corrosion layer and curing to form a base film;
[0119] The bottom layer is made of acrylic resin paint on the outer surface of the cured anti-corrosion layer. After coating, it is placed at 100℃ for curing for 30-50 minutes.
[0120] S5. Coating a hydrophilic surface layer on the outer side of the base film and performing light curing.
[0121] The hydrophilic surface layer is coated with a photosensitive hydrophilic acrylic resin. When coating the photosensitive hydrophilic acrylic resin, a coater is first used to coat the photosensitive hydrophilic acrylic resin on the outer surface of the bottom layer, and then a curing agent is used to cure the coated photosensitive hydrophilic acrylic resin to obtain a hydrophilic surface layer. The thickness of the hydrophilic surface layer is 40-60 microns, and the thickness of the bottom layer is 20-30 microns.
[0122] The preparation steps of photosensitive hydrophilic acrylic resin are as follows:
[0123] A. Add solvent to the reaction vessel and heat the reaction vessel to 50-60°C;
[0124] B. adding an initiator to a hydrophilic monomer to form a mixed solution;
[0125] C. Add the mixed solution into a reaction vessel for polymerization reaction, and keep the polymerization temperature for 2.5-3 hours to obtain an acrylate copolymer;
[0126] D. Adding a catalyst, a polymerization inhibitor and a photosensitive monomer to the acrylate copolymer, and heating the reaction container to 120-130° C. to obtain a photosensitive hydrophilic acrylic resin after reaction;
[0127] The solvent is a mixed solvent of ethylene glycol monomethyl ether and toluene in a weight ratio of 1:1:
[0128] The hydrophilic monomers are acrylic acid, hydroxypropyl acrylate and butyl acrylate in a weight ratio of 36:65:64;
[0129] The initiator is an azo initiator, and the initiator is azobisisobutyronitrile;
[0130] The catalyst is chiral thiourea;
[0131] The polymerization inhibitor is copper cyclohexaneate;
[0132] The photosensitive monomer is glycidyl methacrylate.
[0133] The hydrophilic aluminum foil produced by the solution with patent number CN114798388B was used as a comparative example. The test plate was coated and the adhesion and hydrophilicity were measured with reference to the standard "YS / T95.2-2009 Aluminum Foil for Air Conditioner Heat Sink". The performance of the products of Examples 1-3 and the comparative example products, and the test results are shown in the following table;
[0134] Example 1 Example 2 Example 3 Comparative Example Initial hydrophilic angle (°) 5 3 4 4 Continuous hydrophilic angle (°) 9 8 8 9 150℃20d peeling rate (%) <1 <1 <1 5
[0135] It can be seen from the data in the above table that the performance of the aluminum alloy described in the present invention is greatly improved.
[0136] The present invention records a hydrophilic aluminum foil for air conditioner heat sinks, which uses epoxy acrylic resin with simple raw material sources and simple synthesis process as the main raw material, and uses a light-curing hydrophilic coating, which has a low curing temperature and relatively low production requirements, and can greatly reduce production costs. At the same time, less solvent is required in the production process, and the overall use is relatively environmentally friendly.
[0137] The hydrophilic coating of the hydrophilic aluminum foil adopts the method of combining a bottom layer and a hydrophilic surface layer, and both the bottom layer and the hydrophilic surface layer are based on acrylic resin, and the compatibility between the two is good, which is conducive to the hydrophilic surface layer to penetrate into the bottom film, resulting in better adhesion. It will not fall off during long-term use, and the use effect is good.
[0138] The hydrophilic aluminum foil has strong overall hydrophilicity. When in use, the initial water contact angle is less than 5°, and it has long-lasting continuous hydrophilicity. It also has a good heat resistance limit, can effectively avoid changes and cracking problems caused by high temperature, has good use effect, and has good use prospects.
[0139] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A hydrophilic aluminum foil for air conditioner radiator, characterized in that: It includes an aluminum foil body and a protective layer arranged on the outside of the aluminum foil body, wherein the protective layer includes an anti-corrosion layer and a photocurable hydrophilic layer, wherein the anti-corrosion layer is arranged on the outer surface of the aluminum foil body by thermal spraying, and the photocurable hydrophilic layer is coated on the outside of the anti-corrosion layer and is photocured by a curing machine.
2. The hydrophilic aluminum foil for air conditioner radiator according to claim 1, characterized in that: The hydrophilic layer comprises a bottom layer and a hydrophilic surface layer. The bottom layer is coated on the outside of the anti-corrosion layer. After the bottom layer is cured, the hydrophilic surface layer is coated on the outside of the bottom layer.
3. The hydrophilic aluminum foil for air conditioner radiator according to claim 2, characterized in that: The preparation steps of hydrophilic aluminum foil for air conditioner radiator are as follows: S1. Select an aluminum foil body of standard size and then pre-treat the aluminum foil body; S2, spraying the anti-corrosion coating on the outer surface of the aluminum foil body by thermal spraying; S3, high temperature curing anticorrosive layer; S4, coating a base layer on the outside of the anti-corrosion layer and curing to form a base film; S5. Coating a hydrophilic surface layer on the outer side of the base film and performing light curing.
4. The hydrophilic aluminum foil for air conditioner radiator according to claim 3, characterized in that: The steps of pre-treating the aluminum foil body in step S1 are as follows: After immersing the aluminum foil in a 5% NaOH solution for 25-40 seconds, rinse the aluminum foil with deionized water for 2-5 minutes; The rinsed aluminum foil is soaked in a 30% nitric acid solution for 50-65 seconds, then rinsed with deionized water for 2-5 minutes, and then air-dried.
5. The hydrophilic aluminum foil for air conditioner radiator according to claim 4, characterized in that: In step S2, the anti-corrosion coating is sprayed on the outer surface of the aluminum foil body by using plasma spraying technology.
6. The hydrophilic aluminum foil for air conditioner radiator according to claim 5, characterized in that: When the anti-corrosion layer is cured at high temperature in step S3, the product is placed at 100° C. for 20-25 minutes, and then placed at 150-300° C. for 1-2 hours to obtain a cured anti-corrosion layer.
7. The hydrophilic aluminum foil for air conditioner radiator according to claim 6, characterized in that: The anticorrosive coating comprises the following components in parts by weight: 18-20 parts of organic silicon resin, 25-35 parts of polyurethane resin, 6-8 parts of nano titanium dioxide, 3-5 parts of nano aluminum powder, 2-10 parts of curing agent, 8-15 parts of diluent and 10-20 parts of deionized water; The curing agent is polyamide resin, and the diluent is any one of diethylene glycol ethyl ether and butyl acetate.
8. The hydrophilic aluminum foil for air conditioner radiator according to claim 7, characterized in that: The bottom layer in step S4 is coated with acrylic resin on the outer surface of the cured anti-corrosion layer, and after coating, it is placed at 100° C. for curing for 30-50 minutes.
9. The hydrophilic aluminum foil for air conditioner radiator according to claim 8, characterized in that: In step S5, the hydrophilic surface layer is formed by coating with a photosensitive hydrophilic acrylic resin. When coating the photosensitive hydrophilic acrylic resin, a coater is first used to coat the photosensitive hydrophilic acrylic resin on the outer surface of the bottom layer, and then a curing agent is used to cure the coated photosensitive hydrophilic acrylic resin to obtain a hydrophilic surface layer. The thickness of the hydrophilic surface layer is 40-60 microns, and the thickness of the bottom layer is 20-30 microns.
10. The hydrophilic aluminum foil for air conditioner radiator according to claim 9, characterized in that: The preparation steps of the photosensitive hydrophilic acrylic resin are as follows: A. Add solvent to the reaction vessel and heat the reaction vessel to 50-60°C; B. adding an initiator to a hydrophilic monomer to form a mixed solution; C. Add the mixed solution into a reaction vessel for polymerization reaction, and keep the polymerization temperature for 2.5-3 hours to obtain an acrylate copolymer; D. Adding a catalyst, a polymerization inhibitor and a photosensitive monomer to the acrylate copolymer, and heating the reaction container to 120-130° C. to obtain a photosensitive hydrophilic acrylic resin after reaction; The solvent is a mixed solvent of ethylene glycol monomethyl ether and toluene in a weight ratio of 1:1: The hydrophilic monomers are acrylic acid, hydroxypropyl acrylate and butyl acrylate in a weight ratio of 36:65:64; The initiator is an azo initiator, and the initiator is one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate; The catalyst is one of chiral thiourea and tetrabutylammonium bromide; The polymerization inhibitor is one of hydroquinone, tert-butylcatechol and copper naphthenate; The photosensitive monomer is glycidyl methacrylate.
Citation Information
Patent Citations
Superhydrophilic antibacterial aluminum foil
CN114798388B